The art of censorship in postwar Japan - Cather, Kirsten (Studies of the Weatherhead East Asian Institute, Columbia University., 2012)
"In 2002 a manga (comic book) was for the first time successfully charged with the crime of obscenity in the Japanese courts. In The Art of Censorship Kirsten Cather traces how this case represents the most recent in a long line of sensational landmark obscenity trials that have dotted the history of postwar Japan. The objects of these trials range from a highbrow literary translation of Lady Chatterley's Lover and modern adaptations and reprintings of Edo-period pornographic literary "classics" by authors such as Nagai Kafu to soft core and hard core pornographic films, including a collection of still photographs and the script from Oshima Nagisa's In the Realm of the Senses, as well as adult manga. At stake in each case was the establishment of a new hierarchy for law and culture, determining, in other words, to what extent the constitutional guarantee of free expression would extend to art, artist, and audience. The work draws on diverse sources, including trial transcripts and verdicts, literary and film theory, legal scholarship, and surrounding debates in artistic journals and the press. By combining a careful analysis of the legal cases with a detailed rendering of cultural, historical, and political contexts, Cather demonstrates how legal arguments are enmeshed in a broader web of cultural forces. She offers an original, interdisciplinary analysis that shows how art and law nurtured one another even as they clashed and demonstrates the dynamic relationship between culture and law, society and politics in postwar Japan. The Art of Censorship will appeal to those interested in literary and visual studies, censorship, and the recent field of affect studies. It will also find a broad readership among cultural historians of the postwar period and fans of the works and genres discussed."--Project Muse